Instrumentalsätze im Deutschen und Polnischen - Koniuszaniec, Gabriela (Studia Germanica Posnaniensia, 2018)
The author's object of analysis are instrumental clauses in Polish, which are mostly reduced to participial constructions, and their translational equivalents in German. The corpus of sentences containing such subordinate clauses has been taken from Th. Mann's novel "Bekenntnisse des Hochstaplers Felix Krull". The syndetic structure of instrumental clauses in German is marked by the complementizers indem, damit, dass, dadurch dass. It depends on the translator's creativity to overcome the difficulties arising from the polyfunctional use of these complementizers, especially indem.